2015
DOI: 10.35652/igjps.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Extraction & Characterization of Chitin & Chitosan from Bionetria CBNR BKRR, Synthesis of their Bionanocomposites and Study of their Application

Abstract: Chitin and chitosan hold a great economic value due to their versatile biological activities and chemical applications, mainly in medical and pharmaceutical. Bionectria CBNR KRRR, isolated from the marine soils of Pichavaram, Tamil Nadu was used for the economic production of Chitin and Chitosan using three different media-Sabouraud sucrose broth, Hesseltine and Anderson medium, Andrade et al medium. The polysaccharides were extracted by alkali-acid treatment, and characterized by infrared spectroscopy. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The band at 1068 cm −1 confirms the C-O functional group [ 23 , 24 ]. The functional groups of the electrospun commercial CS/TFA-DCM nanofiber are similar to the bands 3429 cm −1 , 1651 cm −1 , and 1417 cm −1 of the commercial chitosan used in the study reported by Kumirska et al (2010); thus, the chitosan nanofibers were structurally similar to chitosan [ 25 , 26 ], not chitin.…”
Section: Resultssupporting
confidence: 76%
“…The band at 1068 cm −1 confirms the C-O functional group [ 23 , 24 ]. The functional groups of the electrospun commercial CS/TFA-DCM nanofiber are similar to the bands 3429 cm −1 , 1651 cm −1 , and 1417 cm −1 of the commercial chitosan used in the study reported by Kumirska et al (2010); thus, the chitosan nanofibers were structurally similar to chitosan [ 25 , 26 ], not chitin.…”
Section: Resultssupporting
confidence: 76%
“…Significant shifts of peaks in the spectrum of CNPs from peaks in the spectrum of the chitosan standard indicate a significant role of functional groups in the CNPs biosynthesis. The presence of bands at 3442 cm −1 in the chitosan standard sample indicates strong dimeric OH stretch 56 . Moreover, on the formation of nanoparticles, the hydroxyl (OH) stretching peak at wavelength 3442.09 cm −1 found in the spectrum of chitosan standard shifted to 3326.66 cm −1 which indicates the stretching vibrations of OH groups (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Krishnaveni and Ragunathan 56 , 58 reported that the bands at 1655 cm −1 , and those at 1641, 1642 cm −1 indicate the presence of the amide I region. Further, the band at 1654.98 cm −1 (around 1655 cm −1 ) indicates the stretching vibration of type I amide.…”
Section: Resultsmentioning
confidence: 99%
“…CMS was fabricated from a chitosan-based porous sheet via laser micromachining (Figure a). Chitosan is known to have high energy absorbance in the UV wavelength region (300–400 nm) . Hence, the femtosecond-pulsed UV laser with a 343 nm wavelength and 190 fs pulse duration was used to micromachine the chitosan-based porous sheet.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan is known to have high energy absorbance in the UV wavelength region (300−400 nm). 28 Hence, the femtosecond-pulsed UV laser with a 343 nm wavelength and 190 fs pulse duration was used to micromachine the chitosan-based porous sheet. In order to minimize damage to the sheet by the laser, the laser power was optimized by testing several samples.…”
Section: Resultsmentioning
confidence: 99%